2019
DOI: 10.1155/2019/5985207
|View full text |Cite
|
Sign up to set email alerts
|

Development of Novel Topical Cosmeceutical Formulations from Nigella sativa L. with Antimicrobial Activity against Acne-Causing Microorganisms

Abstract: Acne vulgaris occurs due to the inflammation of sebaceous follicles in the skin. It is triggered by the activity of some bacterial species like Propionibacterium acnes, Staphylococcus aureus, and Staphylococcus epidermidis. Acquisition of antibiotic resistance by these microorganisms and adverse effects associated with the current treatment regimens necessitate the introduction of novel therapeutic agents for acne vulgaris. Thus, this study was undertaken to develop novel gel formulations from seeds of Nigella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…Topical N. sativa gel exhibited a greater zone of hemolysis against S. aureus (10.6 mm) but a slightly smaller zone of hemolysis against C. acnes (9.0 mm) compared to the commercial synthetic anti-acne gel (8.3 mm and 10.5 mm, respectively). 20 Acute local irritation tests of this 15% topical extract showed minimal adverse side effects, with only 14% of human participants (n = 50) displaying signs of hypersensitivity while 86% were unaffected.…”
Section: Acne Vulgarismentioning
confidence: 88%
See 1 more Smart Citation
“…Topical N. sativa gel exhibited a greater zone of hemolysis against S. aureus (10.6 mm) but a slightly smaller zone of hemolysis against C. acnes (9.0 mm) compared to the commercial synthetic anti-acne gel (8.3 mm and 10.5 mm, respectively). 20 Acute local irritation tests of this 15% topical extract showed minimal adverse side effects, with only 14% of human participants (n = 50) displaying signs of hypersensitivity while 86% were unaffected.…”
Section: Acne Vulgarismentioning
confidence: 88%
“…The multifactorial pathogenesis of acne vulgaris is associated with androgen-induced increased sebum production, altered keratinization, inflammation, and bacterial colonization of hair follicles by Cutibacterium acnes (C. acnes), Staphylococcus epidermidis (S. epidermidis), and Staphylococcus aureus (S. aureus). 20,21 Treatment options for acne vulgaris vary from topical retinoids, benzoyl peroxide, salicylic acid, topical antibiotics, and oral antibiotics. 22 However, irritation and acquired antibiotic resistance are commonly reported adverse side effects, calling for further investigation into natural remedies for acne vulgaris.…”
Section: Acne Vulgarismentioning
confidence: 99%
“…Antibacterial extracts were screened for their effect on S. aureusas well as P. acnesusing the gel well diffusion method. Results concluded that antibacterial property of topical gel formulation prepared using ethylacetate extract of Nigella sativa proved its applicability as an alternative to existing remedies against dermal acne [1].…”
Section: Research Questionmentioning
confidence: 98%
“…Because of versatility and wider surface area, skin epidermis has been considered a promising route for drug administration. Topical drug delivery system designed to distribute a variety of drugs by diffusion through the layers of the skin to the body [1]. Gels are transparent to opaque semisolids and have a gelling component that interferes with the creation of a colloidal 3D network structure.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggest acne vulgaris ameliorating properties of black cumin seeds ( Table 9 ). Nawarathne et al showed that the application of three topical gels formulated with ethyl acetate extract of black cumin seeds for 30 days inhibited growth of S. aureus and P. acnes [ 224 ]. Application of TQ-loaded ethosomes gel formulation (THQ–EGF) has been shown to decline the number and size of sebaceous glands in rats suggesting TQ as an effective treatment option for acne vulgaris [ 225 ].…”
Section: Benefits Of Black Cumin On Human Health and Disease Conditionsmentioning
confidence: 99%